Odontogenic cysts: A retrospective clinical analytic study of 632 cases diagnosed in Benghazi- Libya - El Hasi, Nagla; Mussa, Asma; Elmurtadi, Ali (Libyan Journal of Dentistry, 2021)
Background: Odontogenic cysts (OCs) are the most common cause of chronic swellings of the jaws as well as the most frequent lesions encountered in oral cavity. Clinical data about the OCs in the Libyan population is scant. Therefore, the objective of this study was to determine the prevalence of all histologically diagnosed OCs and demographics of OCs of Libyan sample over a 28-year period and to compare results with other international studies. Material and Methods: All entries for odontogenic cysts occurring during 1990–2018 inclusive at oral Pathology department, faculty of dentistry, Benghazi University, Libya, were retrieved and analysed for demographic data; mainly sex, age and site. Results: A total of 8995 oral biopsies, 7.03% were odontogenic cysts. Radicular cyst was the most common odontogenic cyst comprising 52.53% of cases, followed by dentigerous cyst (15.03%), odontogenic keratocyst (10.28%) and residual cysts (7.91%). There were 363 specimens for males (57.4%) and 265 for females (41.9%). Odontogenic cysts occurred in a a mean age of 30.2 years. The most common location was maxillary anterior-premolar region (35.9%). Conclusions: These data are important to assess geographic differences in the prevalence of lesions and to allow clinicians to make realistic judgments in counselling patients before biopsy about the probability of diagnosis and risks associated with nonspecific clinical or radiographic lesions.